On the modelling of pore pressure developments below cyclically loaded offshore gravity foundations. Issue 2 (6th April 2017) - van Wijngaarden, Martijn
Abstract : Saturated sands show an increase in pore pressure under cyclic loading in undrained conditions. A challenge in modelling pore pressures below offshore gravity foundations is the effect of random or irregular cyclic loads. In literature, a method is proposed in which equivalent loads with a constant period and a constant amplitude are used. In this paper, a method is presented which takes both the irregular nature of cyclic loads and the real load development in time into account. The cyclic loads are derived in the frequency domain for a gravity foundation of an offshore wind turbine. The irregular loads are simulated with a random phase model. The pore pressures are modelled in a one-dimensional model including three-dimensional dissipation. The results show that the irregular nature of the cyclic loads results in a significant spread in maximum pore pressures below the foundation.